KOMUNIKASI ORGANISASI BERPENGARUH TERHADAP MOTIVASI KERJA KARYAWAN PT SUMITOMO WIRING SYSTEMS BATAM INDONESIA - Syahrani; Purwanti, Angel (LPPM Universitas Putera Batam, 2022)
Work motivation is a condition or energy that directs employees to achieve company goals. currently, the development of organizational communication sees communication as one of the most dominant and important activities in the organization and can motivate employees. the purpose of this research is to reveal how the role of communication that occurs in the company Sumitomo wiring systems Batam. this study uses quantitative methods. with the determination of the sample using random sampling, the number of samples in this study were 180 respondents with 23 questions on the questionnaire. the results of the study obtained a t value of 10,758> 1,653 and a sig value which was smaller than 0.005 which concluded that organizational communication had a significant influence on employee motivation at PT Sumitomo wiring systems, the results of the coefficient of determination test obtained a measure of organizational communication explaining employee motivation by 39%